2016
DOI: 10.1080/08990220.2016.1197114
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the brain regions associated with acute spasticity in patients diagnosed with an ischemic stroke

Abstract: Spasticity is a common impairment found in patients that have been diagnosed with a stroke. Little is known about the pathophysiology of spasticity at the level of the brain. This retrospective study was performed to identify an association between the area of the brain affected by an ischemic stroke and the presence of acute spasticity. Physical and occupational therapy assessments from all patients (n = 441) that had suffered a stroke and were admitted into a local hospital over a 4-year period were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
3
20
1
Order By: Relevance
“…[ 31 ] The result of this study is consistent with that of past studies reporting that an association of spasticity with the gray matter includes the corticospinal tract pathway. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] The result of this study is consistent with that of past studies reporting that an association of spasticity with the gray matter includes the corticospinal tract pathway. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although the reported prevalence of spasticity following stroke is highly variable, ranging from 4 to 42.6%[25], few studies have investigated the effects of brain lesions on spasticity in patients with stroke[6, 7]. Nonetheless, several studies have demonstrated how brain lesions can contribute to the development of spasticity in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…The internal capsule is supplied by the middle cerebral artery. Damage in this region can result in motor impairment, particularly in the upper limbs 42,43 . The negative correlation observed in the two evaluations using the Motor Assessment Scale, Box and Block Test, and Chedoke-McMaster (arm) suggest that this structure can be used as a marker for the indication of VRT combined with conventional rehabilitation.…”
Section: Discussionmentioning
confidence: 99%